A Regular Input-Output Model with Decreasing Marginal Returns - Jaksch, Hans Jurgen (Review of Economic Studies, 1960)
A Regular Input-Output Model with Decreasing Marginal Returns Get access Hans Jurgen Jaksch Hans Jurgen Jaksch Frankfurt am Main Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 2, February 1960, Pages 135–138, https://doi.org/10.2307/2296136 Published: 01 February 1960